Planos nutricionais e seus efeitos sobre índices produtivos, fisiológicos e econômicos de frangos de corte - Martins, Julyana Machado da Silva (2014)
The aimed of this study was to evaluate nutritional plans effects on production, physiological and economic rates of Hubbard Flex broiler breed. The experiment was completely randomized, with five treatments, being the reference treatment based on nutrient and energy levels indicated by Rostagno et al. (2011) and the others calculated from this ( -3 % , -1.5 % , + 1.5 % and + 3 % ). Cumulative performance was evaluated at the end of each growing phase, at 35 and 42 days old superficial and body temperatures, at 42 days old carcass yield, relative organs weights, breast composition and economic viability. At 35 and 42 days old energy increased and nutrient levels reduced feed intake and improved feed conversion. A better breast composition was observed better with increased nutrient and energy levels. Costs increased with increasing dietary plans. Wing, back and cloacal temperature were not affected by dietary plans, and consequently superficial body rates temperatures. Effect on energetic and nutritional levels increased on liver, gizzard and the small intestine weights were observed. Were conclude that increasing nutrient and energy levels had better feed intake , feed conversion rate, economic efficiency and breast composition, as body temperature was not affected. However , economic analysis showed worst result to higher levels within each plan.